Trafficking of TRPP2 by PACS proteins represents a novel mechanism of ion channel regulation - Koettgen, Michael; Benzing, Thomas; Simmen, Thomas; Tauber, Robert; Buchholz, Björn; Feliciangeli, Sylvain; Huber, Tobias B.; Schermer, Bernhard; Kramer-Zucker, Albrecht; Höpker, Katja; Simmen, Katia Carmine; Tschucke, Christoph Carl; et al. (EMBO Journal, 2005)
The trafficking of ion channels to the plasma membrane is tightly controlled to ensure the proper regulation of intracellular ion homeostasis and signal transduction. Mutations of polycystin- 2, a member of the TRP family of cation channels, cause autosomal dominant polycystic kidney disease, a disorder characterized by renal cysts and progressive renal failure. Polycystin- 2 functions as a calcium- permeable nonselective cation channel; however, it is disputed whether polycystin- 2 resides and acts at the plasma membrane or endoplasmic reticulum ( ER). We show that the subcellular localization and function of polycystin- 2 are directed by phosphofurin acidic cluster sorting protein ( PACS)- 1 and PACS- 2, two adaptor proteins that recognize an acidic cluster in the carboxy- terminal domain of polycystin- 2. Binding to these adaptor proteins is regulated by the phosphorylation of polycystin- 2 by the protein kinase casein kinase 2, required for the routing of polycystin- 2 between ER, Golgi and plasma membrane compartments. Our paradigm that polycystin- 2 is sorted to and active at both ER and plasma membrane reconciles the previously incongruent views of its localization and function. Furthermore, PACS proteins may represent a novel molecular mechanism for ion channel trafficking, directing acidic cluster- containing ion channels to distinct subcellular compartments.
Keywords: PACS; polycystin-2; TRPP2